Analisis Dampak Covid-19 di Era Pasca Covid pada Operasional Penerbangan di Bandar Udara Sam Ratulangi Manado - Tombeng, Marthen; Walansendow, Agustinus; Walansendow, Dio Joshua (Jurnal Ilmu Pariwisata, 2024)
This research is about Analysis of the Impact of Covid-19 in the Post-Covid Era on Flight Operations at Sam Ratulangi Airport, Manado. The research aims to explain what happened as a result of the Covid 19 pandemic in flight operations at Sam Ratulangi Airport, Manado. Besides that, it analyzes descriptively how the impact of Covid-19 on flight operations at Sam Ratulangi Airport in Manado, including in the post-covid-19 era. This research is a qualitative research using data collection methods with interviews, field observations and online surveys in a descriptive way about opinions on flight operational at Sam Ratulangi Manado airport and opinions about the use of technology in dealing with Covid-19. The results of the study show that information about the businesses carried out during Covid-19 at Sam Ratulangi Airport where there is a partnership assistance as good practice by the three fostered partners as well as through the distribution of this partnership program, small and medium businesses which are expected to grow and develop with a competitive program. In addition, there have been efforts to handle post-Covid-19 at Sam Ratulangi Airport where thre is implementation of health protocols is key in implementing airport activities to minimize the risk of spreading Covid-19. There are new normal activities during and post Covid 19 at Sam Ratulangi Airport operations, namely: wearing masks, measuring body temperature, handling people with symptoms, washing hands, keeping a safe distance, proof of vaccine information, checking in early, implementing SOP (Standard Operational Procedure), installing information media as socialization of health protocols, provision of special facilities, provision of disinfectant facilities, 139 ensuring tenant/third party operations, spraying disinfectants for cabin baggage, choosing touchless services, self check-in, cashless transactions, implementing operational pattern adjustments, security guarantees, operational reporting. Through an online survey about the use of technology in dealing with Covid, namely by utilizing applications namely Care for Protect, Safe Homes, United to Against Covid-19, M-Health and telemedicine applications. This means that various parties, both the government and the community have made great efforts in handling Covid-19 by using various digital applications and information technology.